Inadvertent consequences of fishing: the case of the sex‐changing shrimp. (15th April 2013) - Côté, Isabelle M.; Bradshaw, Corey
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" id="jane12074-blkfxd-0001" position="anchor" orientation="portrait"> The Hokkai shrimp Pandalus latirostris starts life as a male, but eventually turns into a female given the right size and social conditions. The traps used in the fishery targeting this species selectively retain the larger females, leaving a severely male‐biased sex ratio in nature and social conditions that bear no resemblance to those that prompted (or prevented) sex change. Photo: Susumu Chiba </boxed-text> <mixed-citation id="jane12074-cit-0001" publication-type="journal" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink"> <string-name> <surname>Chiba</surname>, <given-names>S.</given-names></string-name>, <string-name><surname>Yoshino</surname>, <given-names>K.</given-names></string-name>, <string-name><surname>Kanaiwa</surname>, <given-names>M.</given-names></string-name>, <string-name><surname>Kawajiri</surname>, <given-names>T.</given-names></string-name> & <string-name><surname>Goshima</surname>, <given-names>S.</given-names></string-name> (<year>2013</year>) Maladaptive sex ratio adjustment by a sex‐changing shrimp in selective fishing environments . <source content-type="journalTitle">Journal of Animal Ecology</source>, <volume>82</volume>, <fpage>631</fpage>–<lpage>640</lpage>.</mixed-citation> Fishing can have many unintended consequences. In this issue, Chiba et al. (2013) demonstrate that size‐selective harvesting of a sex‐changing shrimp effectively voids their normally adaptive adjustments to population sex ratio. The shrimp's 'decision' to change sex depends largely on the relative abundance of mature males and females in early summer, before fishing begins. However, fishing traps selectively retain females, leading to heavily male‐biased sex ratios at the onset of autumn breeding that are different from the ratios that influenced sex‐change decisions. Although this phenomenon is not yet expressed in catch trends, maladaptive sex‐change decisions could ultimately affect population productivity and persistence.